DETERMINASI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH: PERAN SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERNAL PEMERINTAH (SPIP), DAN KEPATUHAN REGULASI - Bayu Pratama; Rahmat Yuliansyah; Krisnando; Defi Damayanti; Krisnando Krisnando (Bajang Institute, 2026)
Abstract: This study aims to examine whether accounting information systems, internal control systems, and compliance with accounting regulations affect the quality of financial reports in the DKI Jakarta regional government. This research employs an associative research design with a quantitative approach, using multiple linear regression analysis with SPSS version 23. The population of this study consists of all Civil Servants (ASN) working in Regional Apparatus Organizations (OPD) within the DKI Jakarta Provincial Government. However, not all ASN were included as the unit of analysis; the study specifically focuses on those directly involved in the management and preparation of financial reports. The sample was determined using the Slovin formula, resulting in 100 respondents. The sampling technique applied was purposive sampling, based on specific criteria relevant to the research objectives. The results show that, partially, internal control systems and compliance with accounting regulations have a significant effect on the quality of financial reports, while accounting information systems do not have a significant effect on the quality of financial reports.